Answered

Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Ask your questions and receive precise answers from experienced professionals across different disciplines. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

x^2 - 4x + 3 how do I factor the expression completely

Sagot :

bx must be the sum of the numbers in the bracket and c must be the product. So we need to choose 2 numbers that multiply to make 3 and add to make -4.

A negative x negative = positive so
-3*-1=3
-3-1=-4

Therefore:
(x-3)(x-1)
[tex]x^2 - 4x + 3=\\ x^2-x-3x+3=\\ x(x-1)-3(x-1)=\\ (x-3)(x-1)[/tex]